THE INTERTEXTUAL NATURE OF FEMAIE IMAGES IN THE WORKS OF SAFUAN SHAIMERDENOV (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
The article analyzes the typology of female images in the works of writer Safuan Shaimerdenov from the perspectives of intertextuality and national identity. The primary goal of the research is to identify the typological characteristics of female characters in the author's works and to uncover their role in reflecting national identity.The depiction of women in literature is one of the essential tools for conveying national identity. In Kazakh prose, portraying national values, spiritual heritage, and adaptation to contemporary challenges through female characters is a pressing issue in modern literary studies. Shaimerdenov’s female characters represent significant aspects of national identity by integrating the traditional values of the Kazakh people with the innovations of modern times.The study focuses on the characters Bibigul, Kargash, Aspet, and Inesh from prominent works such as Mezgil, Kargash, Mazhnun Tal, and Inesh. Content analysis, intertextual analysis, typological methods, and linguo-cognitive approaches were employed. The artistic techniques used by the author to convey national identity, as well as the characters’ behaviors and spiritual worlds, were examined in detail. Additionally, the intertextual connections of Shaimerdenov’s characters with similar images in other literary works were analyzed.The results of the article highlight the unique typological role of female images in Kazakh literature and their significance in shaping national consciousness. The scientific analyses conducted in the study provide deeper insights into the artistic features of female characters in Kazakh literature and offer a fresh perspective on the issues of national identity.